The Influence of Family Socioeconomic Status in The Health Financing Method Model for Vulnerable Groups in Batanghari Regency - Noerjoedianto, Dwi; Kalsum, Ummi; Ridwan, M; Halim, Rd; Subandi, Andi (Jurnal Kesmas Jambi, 2025)
Following the enactment of Law No. 17 of 2023 on Health, which stipulates that nominal amounts do not determine the allocation of health financing, provincial and district governments are have been striving to implement teh law based on regional priority scales. The World Health Organization (WHO) recommends six patterns and seven health financing mechanisms, which have been variably adopted across regions, including in Jambi Province. The study aims to examine the influence of family socioeconomic status on the selection of health financing models among vulnerable population group. A quantitative approach with a cross-sectional design was employed, involving 271 households as the sample. Data were analyzed using multiple logistic regression. The finding indicate that socioeconomic status has a positive influence (0.945) on the ability to afford healthcare services. This means that for every one-unit increase in socioeconomic status, the likelihood of being able to purchase healthcare increases by 0.945 times. The predictive model for the choice of health financing mechanisms reveals a preference for per package payments, Diagnosis Related Groups (DRGs), monthly salaries, and fee-for-service models. Conversely, global budgets, capitation, and pre-payment reimbursement schemes were the least preferred. These finding inderscore the importance of socioeconomics factors in determining access to and preferences for health financing mechanisms, particularly among vulnerable groups.